Perancangan Aplikasi Mobile Sig Untuk Pemantauan Sebaran Penyakit Di Kabupaten Cianjur - Somantri, S; Hermanto, H; Darmawan, Muhammad Rifqi (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
Cianjur Regency is one of the districts with the largest population in West Java. Therefore, this research proposes designing a Geographic Information System (GIS) mobile application in an effort to increase the effectiveness of monitoring the spread of disease in Cianjur Regency. This research uses a waterfall-based software development methodology which includes analysis, design, implementation, testing and maintenance stages. At the analysis stage, overall system requirements are determined, including by determining software and hardware requirements. The design stage involves creating data flow diagrams and user interface design. The implementation was carried out using Android-based mobile development technology using Kotlin Jetpack Compose and Laravel. This application is equipped with main features such as an attractive display, an interactive map that displays the distribution of disease cases along with education about each disease. Application testing is carried out using the Black Box and Posman testing methods to ensure that each function runs according to predetermined specifications. Test results show that this application can facilitate monitoring the spread of disease quite well. Apart from that, it is hoped that this application will help the government and health workers to take appropriate action to prevent the further spread of disease and for local communities to be able to find out what phenomena are occurring in their area along with education about the disease.